Statistical thinking skills included in primary school mathematics books (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify (statistical thinking skills included in mathematics textbooks for the primary stage for the academic year 2021-2022 AD). Mathematics books for the primary stage, which are (6) mathematics books (student’s book only) for the academic year (2021-2022 AD), and the idea unit (explicit, implicit) was adopted as a recording unit, and repetitions as a counting unit, and to achieve the goal of the research, the researcher built an initial list of thinking skills The statistical validity of the tool was confirmed by presenting it to the arbitrators, and the final list included (40) indicators and (26) sub-skills distributed on (4) major skills of statistical thinking. Statistical thinking), the validity of the analysis was confirmed, and the stability of the analysis by the two methods over time (the researcher with herself after a certain period of time) And through the others (the researcher with other analysts), and calculating the percentage of agreement using the Holsti equation. , but in varying proportions, and in an unbalanced manner, and recommendations were made, including: (observing balance when including statistical thinking skills in the content of mathematics books decided at the primary stage, in proportion to the scientific level of the subject, and taking into account the various studies and the diversity proposals) Preparatory school mathematics according to statistical thinking skills and the extent to which students have acquired them, conducting descriptive studies to determine the extent to which learners possess statistical thinking skills and for different educational stages